1999
DOI: 10.1177/026988119901300303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of diazepam on the fear-potentiated startle reflex and the fear-inhibited light reflex in man

Abstract: It has been shown previously that the amplitude of the acoustic startle reflex is enhanced, and the amplitude of the light reflex reduced, when subjects anticipate an aversive event, compared to periods when subjects are resting ('fear-potentiated startle reflex' and 'fear-inhibited light reflex'). We examined whether the anxiolytic diazepam would reverse the effects of threat on the startle and pupillary reflexes. Twelve male volunteers participated in three weekly sessions in which they received oral treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
5
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(107 citation statements)
references
References 37 publications
11
84
5
7
Order By: Relevance
“…In none of the studies did benzodiazepine reduced significantly fear-potentiated startle to a short duration threat cue. These results have been confirmed by some (Riba et al 1999;Scaife et al 2005) but not others (Bitsios et al 1999;Riba et al 2001)(see Walker and Davis 2002b) for a discussion of issues related to the effect of benzodiazepines on fear-potentiated startle). Recently, we replicated the lack of effect of benzodiazepines on fear-potentiated startle to a threat cue using alprazolam (Grillon et al 2006a).…”
Section: Empirical Studies Of Sustained Anxiety: Psychopharmacologicasupporting
confidence: 55%
“…In none of the studies did benzodiazepine reduced significantly fear-potentiated startle to a short duration threat cue. These results have been confirmed by some (Riba et al 1999;Scaife et al 2005) but not others (Bitsios et al 1999;Riba et al 2001)(see Walker and Davis 2002b) for a discussion of issues related to the effect of benzodiazepines on fear-potentiated startle). Recently, we replicated the lack of effect of benzodiazepines on fear-potentiated startle to a threat cue using alprazolam (Grillon et al 2006a).…”
Section: Empirical Studies Of Sustained Anxiety: Psychopharmacologicasupporting
confidence: 55%
“…Imaging studies in humans have revealed that neural systems that are involved in FPS in rodents also appear to be involved in learned fear in humans, supporting the construct validity of the FPS model in rodents (Phelps et al, 2001;LaBar et al, 1998). Furthermore, as in rats, some reports suggest that FPS can be reduced by diazepam administration in humans, showing some parallels between the predictive validity of the FPS model in rats and humans for anxiety treatment (Bitsios et al, 1999;Patrick et al, 1996; but see Baas et al, 2002). FPS has been shown to be a highly predictive model of anxiety in the rat for both anxiolytic and anxiogenic drugs in humans.…”
Section: Introductionmentioning
confidence: 82%
“…In humans, the FPS effect has been demonstrated with explicit or instructed conditioning as well as with unconditioned stimuli such as violent images (Spence and Runquist, 1958;Grillon et al, 1991;Bitsios et al, 1999;Hamm et al, 1993). Interestingly, patients with post-traumatic stress disorder and panic disorder exhibit increased startle response magnitudes during baseline or stressful conditions (Butler et al, 1990;Grillon et al, 1994;Morgan et al, 1996;Grillon and Morgan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is perhaps surprising then that the effect of benzodiazepines on phasic startle potentiation has been inconsistent, at least in human beings, with positive (Patrick et al, 1996;Bitsios et al, 1999;Riba et al, 2001;Graham et al, 2005) as well as negative Scaife et al, 2005;Grillon et al, 2006) results being reported, and suggestions that the positive effects that have been reported were secondary to sedative effects Fa problem that may be especially pronounced when using absolute difference scores (ie, from trials without to those with the fear stimulus) rather than percent change scores Walker and Davis, 2002b).…”
Section: Discussionmentioning
confidence: 99%